Temporal Evolution and Scaling of Mixing in Turbulent Thermal Convection for Inhomogeneous Boundary Conditions (Advances in Applied Mathematics and Mechanics, 2018)
Numerical simulations of two-dimensional (2D) turbulent thermal convectionfor inhomogeneous boundary condition are investigated using the lattice Boltzmannmethod (LBM). This study mainly appraises the temporal evolution and thescaling behavior of global quantities and of small-scale turbulence properties. Theresearch results show that the flow is dominated by large-scale structures in the turbulenceregime. Mushroom plumes emerge at both ends of each heat source, and smallerplumes increasingly rise. It is found that the gradient of root mean-square (rms) verticalvelocities and the gradient of the rms temperature in the bottom boundary layerdecrease with time evolution. It is further observed that the temporal evolution of theKolmogorov scale, the kinetic-energy dissipation rates and thermal dissipation ratesagree well with the theoretical predictions. It is also observed that there is a rangeof linear scaling in the 2nd-order structure functions of the velocity and temperaturefluctuations and mixed velocity-temperature structure function.